Amplification of Duffy binding protein-encoding gene allows Plasmodium vivax to evade host anti-DBP humoral immunity - Popovici, Jean (Nat Commun, 2020)
Antigenic variation, the capacity to produce a range of variable antigens, is a well-described strategy of Plasmodium and other parasites to evade host immunity. Here, we show that gene amplification is an additional evasion mechanism used by Plasmodium vivax to escape humoral immunity targeting PvDBP, the key ligand involved in reticulocyte invasion. PvDBP gene amplification leads to increased mRNA levels and protects P. vivax in vitro against invasion inhibitory human monoclonal antibodies targeting a conserved binding domain of DBP. Patient samples suggest that parasites with increased pvdbp copy number are able to infect individuals with naturally acquired antibodies highly blocking the binding of PvDBP to the Duffy receptor. These results show that gene copy number variation affect the parasite’s ability to evade anti-PvDBP humoral immunity.